Hutan Tropis Indonesia, Keanekaragaman Hayati, dan Kaitan dengan Pemanasan Global - Ramadhanil Ramadhanil (Biocelebes, 2009)
Indonesia is recognized as one of ”Megabiodiversity countries” in the worldwide which is very rich with biological diversity. It also has been identified as the second largest country which possess tropical rainforest after Brasil. The large area of this tropical rain forest particularly in Indonesia is currently decreased year by year. It is damaged by various human activities such as land converted to plantations in large scale, human resettlement, both legal and illegal logging, hunting as well as forest fire. This human activities are common factors and primary agents contributing to the vast endangerments and extinctions occurring in the past and in the foreseeable future. On the other hand, deforestation and forest degradation have been mentioned to take alarming proportions with severe negative global and regional consequences such as global warming and climate changes. The aim of this paper is to communicate the relationship between the richness of tropical rainforest and global warming or climate changes. Key words: Tropical rainforest, Indonesia, biodiversity and global warming.